A political theory of interspecies mobility justice. Issue 6 (1st November 2020) - Scott, Nicholas
ABSTRACT: This article outlines a political theory of interspecies mobility justice that examines why and how mobility justice should be extended to non-sapien persons. Interspecies mobility justice considers how some species' freedom to move and dwell impinges and relies upon others' diminished mobilities and displacement, and sets out to illuminate better relations among differentially mobile species. Integrating theories of mobility justice and interspecies justice, I argue mobility justice requires citizenship for domesticated animals, denizenship for liminal animals (those adapted to humans without being under their care) and sovereignty for wild animals. To flesh out these three assemblages of interspecies mobility justice, I present analytical vignettes that relate ethnographic observations of people cycling with dogs, crows and orcas to research on animals' mobilities, evolutionary cognition and field observations from urban naturalists. These vignettes clarify moral obligations of interspecies mobility justice using dogs, crows and orcas as paradigmatic case studies. The article concludes by discussing the need to further develop interspecies mobility justice by including non-animal persons. Graphical abstract: uf0001